2022
DOI: 10.1063/5.0122319
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of superconductivity dependence on substrate temperature with thickness of Fe(Se,Te) coated conductors deposited on metal tapes

Abstract: Fe(Se,Te) films of different thicknesses were deposited on metal tapes by pulsed laser deposition at different substrate temperatures. It is found that the substrate temperature dependence of superconductivity changes with the Fe(Se,Te) film thickness. When fabricating thin Fe(Se,Te) films with a thickness of about 150 nm, moderate substrate temperatures are conducive to balancing the influence of texture and stoichiometry on superconductivity, contributing to the obtainment of good superconductivity. When the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…These isolated islands result in the poor grain connectivity and rough surface of FeSeTe film [34]. With increasing T s , the isolated islands become larger due to the enhanced diffusion rate and nucleation rate [35,36], which can be evidenced by the gradually decreasing voids density and the reduced R rms . In addition, the thickness of the FeSeTe films increases with increasing T s within the T s range of 25 • C-400 • C (figure 2(p)), indicating the enhanced diffusion rate and nucleation rate with T s , which is consistent with the results of surface morphologies observed in the AFM images.…”
Section: Resultsmentioning
confidence: 99%
“…These isolated islands result in the poor grain connectivity and rough surface of FeSeTe film [34]. With increasing T s , the isolated islands become larger due to the enhanced diffusion rate and nucleation rate [35,36], which can be evidenced by the gradually decreasing voids density and the reduced R rms . In addition, the thickness of the FeSeTe films increases with increasing T s within the T s range of 25 • C-400 • C (figure 2(p)), indicating the enhanced diffusion rate and nucleation rate with T s , which is consistent with the results of surface morphologies observed in the AFM images.…”
Section: Resultsmentioning
confidence: 99%
“…This is caused by the lack of iron in FST films, resulting in a relatively high amount of the semiconductor elements Se and Te. 37,46 A criterion of 10% and 90% of the normal state resistance at 20 K is used to define 𝑇 zero c and 𝑇 onset c , respectively. The difference between 𝑇 zero c and 𝑇 onset c is defined as the transition width Δ𝑇 c .…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the resistance of all FST films decreases with increasing temperature in the normal state, exhibiting a semiconducting behavior. This is caused by the lack of iron in FST films, resulting in a relatively high amount of the semiconductor elements Se and Te 37,46 . A criterion of 10% and 90% of the normal state resistance at 20 K is used to define Tnormalczero$T_{\mathrm{c}}^{{\mathrm{zero}}}$ and Tnormalconset$T_{\mathrm{c}}^{{\mathrm{onset}}}$, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations